2013
DOI: 10.1038/bmt.2012.250
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of selenium in prevention of oral mucositis in patients undergoing hematopoietic SCT: a randomized clinical trial

Abstract: Oral mucositis (OM) is a complication of high-dose chemotherapy (HDC) followed by hematopoietic SCT (HSCT) with few effective treatments. Selenium has a cytoprotective role via the glutathione peroxidase (Glu.Px) enzyme and prevents chemotherapy-induced toxicities. We performed a double-blind, randomized, placebo-controlled study to evaluate the efficacy of selenium on the prevention of OM in 77 patients with leukemia, undergoing allogeneic HSCT. Thirty-seven patients received oral selenium tablets (200 mcg tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 31 publications
(35 reference statements)
3
45
0
2
Order By: Relevance
“…In addition, we noted that no patient in the NAC group developed grade 4 OM, the most unbearable form of OM, in which oral alimentation is impossible. These findings are in agreement with the results of the study performed by Jahangard-Rafsanjani et al 9 Our results with NAC is also comparable with palifermin, which has been shown to reduce the incidence of grade 4 OM. 32 Palifermin is currently the only drug approved by the US Food and Drug Administration for the prevention of OM in patients with hematologic malignancies who receive HDC.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In addition, we noted that no patient in the NAC group developed grade 4 OM, the most unbearable form of OM, in which oral alimentation is impossible. These findings are in agreement with the results of the study performed by Jahangard-Rafsanjani et al 9 Our results with NAC is also comparable with palifermin, which has been shown to reduce the incidence of grade 4 OM. 32 Palifermin is currently the only drug approved by the US Food and Drug Administration for the prevention of OM in patients with hematologic malignancies who receive HDC.…”
Section: Discussionsupporting
confidence: 83%
“…33 In comparison with palifermin, NAC is relatively inexpensive and has no considerable interactions with antineoplastic drugs. [34][35][36][37] In our study, the overall duration of OM was also significantly shorter in the NAC group whereas in Jahangard-Rafsanjani et al 9 study, only the mean duration of severe OM (grade 3-4) was significantly lower in the intervention group (selenium). However, none of the agents could alter time to onset of OM.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations